Twofeet : an infrastructure-free localization system for large indoor spaces and its applications using smartphones - Loh, Alvin Kai Ip. (2013)
This project implements TwoFeet, an infrastructure-free localization system designed for turn-by-turn navigation within large indoor spaces. While current approaches exist, many of these contending systems necessitate a complex infrastructure and do not take into consideration global scalability, energy efficiency, cost and ease of deployment.